Implementasi Sistem Manajemen Mutu ISO 9001:2015 Pada Perguruan Tinggi Swasta - Muhammad Adie Karya; Qomariyatus Sholihah; Bambang Santoso Haryono (UMSU, 2023)
ISO 9001:2015 is one of the quality assurance systems that implemented in educational units. The Universities must apply the principles of ISO 9001:2015 for successful implementation. This study aims to identify and describe the implementation of management quality of ISO 9001:2015 at Muhammadiyah University of Palangka Raya (UMPR) especially in the implementation of the seven principles of management quality of ISO 9001:2015 which includes; focus on customers, leadership, people involvement, the process of approach, improvement, evidence-based decision making, and management relationship. The type of research that used is descriptive qualitative, data collection is done by in-depth interviews as primary data and documentation data, and literature studies as secondary data. While the data analysis technique that used is interactive model analysis by carrying out three steps, namely (1) condensation data, (2) presentation data, (3) conclusions. The results showed that UMPR had properly implemented the seven quality management principles based on ISO 9001:2015.